2020
DOI: 10.1002/jgf2.307
|View full text |Cite
|
Sign up to set email alerts
|

Qualities required for new graduate visiting nurses: A qualitative study

Abstract: Background:The qualities required for new graduates to become visiting nurses remain unclear. The present study aimed to clarify the qualities required for new graduate visiting nurses.Methods: Semi-structured interviews were conducted with nine home-visiting nurses. Content analysis was conducted by the transcribed data collected from visiting nurses.Results: Years of nursing experience were ranged from 16 to 50. In total, 23 attributes were extracted and categorized. Conclusion:Our findings indicated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…We believe that the previous report 10) was not based on scientific research methods. Another study reported that the characteristics required for new graduate HVNs were 1) relevant basic knowledge, 2) relevant skills, and 3) consideration of the patient and his/ her family members 8) . The findings of the present study are consistent with those findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the previous report 10) was not based on scientific research methods. Another study reported that the characteristics required for new graduate HVNs were 1) relevant basic knowledge, 2) relevant skills, and 3) consideration of the patient and his/ her family members 8) . The findings of the present study are consistent with those findings.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we conducted a qualitative study asking skilled HVNs to describe the characteristics required to perform their duties effectively. Our study results identified the following two major categories for the qualities required for new graduates to work as HVNs: 1) basic knowledge and skills equivalent those required for the national exam for registered nurses, and 2) the appropriate attitude as members of society 8) .…”
Section: Introductionmentioning
confidence: 94%
“…As the healthcare system continues to adapt to the needs of an aging population, newly graduated nurses must be equipped with the knowledge, skills, and attitudes required to provide comprehensive care to older adults. This adaptation includes clinical competencies and qualities such as appropriate attitudes as members of the society, as indicated in a study on the qualities required for newly graduated visiting nurses [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although a previous study has shown that a higher percentage of home-visit nurses discussed EOL decisions with patients compared with hospital nurses ( Joren et al, 2021 ), another reported that hospital nurses were more willing to engage in EOL discussions compared with home-visit nurses because of differences in work settings and level of nursing education ( Albers et al, 2014 ). Furthermore, another study reported that new graduate home-visit nurses experienced difficulties in understanding and providing care based on the patient’s needs ( Akiyama & Fukuyama, 2020 ), and that working at a home-visit nurse station was not a realistic option for them because it required specialized and extensive experience ( Abiodun et al, 2019 ; van Iersel et al, 2016 ). In other words, new graduate home-visit nurses, who face difficulties in assessing the patient’s needs, and inexperienced home-visit nurses find it difficult to determine when to implement EOL discussions that are required by the patient and family; thus, establishing a base from which to determine the appropriate timing to broach the EOL discussions is necessary.…”
mentioning
confidence: 99%